Shape resonance in electron molecule scattering using coupled cluster method - Pal, Sourav; Vaval, Nayana; Sajeev, Y. (Indian Journal of Physics and Proceedings of the Indian Association for the Cultivation of Science, 2007)
The Fock space multi-reference coupled-cluster (FSMRCC) method along with the complex absorbing potential (CAP) is used for the study of the shape resonance energy and width in an electron molecule collision. We study the shape resonances in e(-) -H2CO and e(-) -CO.
Keywords: electron-molecule scattering; multi-reference coupled-cluster

On some aspects of fock-space multi-reference coupled-cluster singles and doubles energies and optical properties - Manohar, Prashant Uday; Shamasundar, K. R.; Bag, Arijit; Vaval, Nayana; Pal, Sourav (Recent progress in coupled cluster methods: theory and applications, 2010)

Study of interatomic coulombic decay of Ne(H2O)(n) (n=1,3) clusters using equation-of-motion coupled-cluster method - Ghosh, Aryya; Pal, Sourav; Vaval, Nayana (Journal of Chemical Physics, 2013)
Interatomic Coulombic decay (ICD) is an efficient and ultrafast radiationless decay mechanism which can be initiated by removal of an electron from the inner-valence shell of an atom or molecule. Generally, the ICD mechanism is prevailed in weakly bound clusters. A very promising approach, known as CAP/EOM-CC, consists of the combination of complex absorbing potential (CAP) with the equation-of-motion coupled-cluster (EOM-CC) method, is applied for the first time to study the nature of the ICD mechanism. We have applied this technique to determine the lifetime of an auto-ionized, inner-valence excited state of the NeH2O, Ne(H2O)(2), and Ne(H2O)(3) systems. The lifetime is found to be very short and decreases significantly with the number of neighboring water molecules. (C) 2013 AIP Publishing LLC.

Structure, stability, and properties of the trans peroxo nitrate radical: the importance of nondynamic correlation - Dutta, Achintya Kumar; Dar, Manzoor; Vaval, Nayana; Pal, Sourav (Journal of Physical Chemistry A, 2014)
We report a comparative single-reference and multireference coupled-cluster investigation on the structure, potential energy surface, and IR spectroscopic properties of the trans peroxo nitrate radical, one of the key intermediates in stratospheric NOx chemistry. The previous single-reference ab initio studies predicted an unbound structure for the trans peroxo nitrate radical. However, our Fock space multireference coupled-cluster calculation confirms a bound structure for the trans peroxo nitrate radical, in accordance with the experimental results reported earlier. Further, the analysis of the potential energy surface in FSMRCC method indicates a well-behaved minima, contrary to the shallow minima predicted by the single-reference coupled-cluster method. The harmonic force field analysis, of various possible isomers of peroxo nitrate also reveals that only the trans structure leads to the experimentally observed IR peak at 1840 cm(-1). The present study highlights the critical importance of nondynamic correlation in predicting the structure and properties of high-energy stratospheric NOx radicals.

Systematic comparison of DFT and CCSD dipole moments, polarizabilities and hyperpolarizabilities (vol 635, pg 168, 2015) - Karne, Anagha S.; Vaval, Nayana; Pal, Sourav; Vasquez-Perez, Jose M.; Koester, Andreas M.; Calaminici, Patrizia (Chemical Physics Letters, 2015)

Systematic comparison of DFT and CCSD dipole moments, polarizabilities and hyperpolarizabilities - Karne, Anagha S.; Vaval, Nayana; Pal, Sourav; Vasquez-Perez, Jose M.; Koester, Andreas M.; Calaminici, Patrizia (Chemical Physics Letters, 2015)
A comparative study of dipole moments, polarizabilities and hyperpolarizabilities of 16 different molecules is performed employing two completely different theoretical approaches namely, density functional theory (DFT) and coupled cluster singles and doubles (CCSD). Both methods include electron correlation. The CCSD method is more accurate but highly expensive. DFT with auxiliary density allows non-iterative solutions which is computational advantage and useful for large molecules. Dipole moments and polarizability calculations from DFT are in very good agreement with CCSD calculations. However, negative hyperpolarizability values from DFT differ significantly from their CCSD counterparts, whereas positive hyperpolarizabilities show reasonable agreement between these methodologies. (C) 2015 Elsevier B.V. All rights reserved.

Search for parity and time reversal violating effects in HgH: relativistic coupled-cluster study - Sasmal, Sudip; Pathak, Himadri; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2016)
The high effective electric field (E-eff) experienced by the unpaired electron in an atom or a molecule is one of the key ingredients in the success of electron electric dipole moment (eEDM) experiment and its precise calculation requires a very accurate theory. We, therefore, employed the Z-vector method in the relativistic coupled-cluster framework and found that HgH has a very large E-eff value (123.2 GV/cm) which makes it a potential candidate for the next generation eEDM experiment. Our study also reveals that it has a large scalar-pseudoscalar (S-PS) P, T-violating interaction constant, W-s = 284.2 kHz. To judge the accuracy of the obtained results, we have calculated parallel and perpendicular magnetic hyperfine structure (HFS) constants and compared with the available experimental values. The results of our calculation are found to be in nice agreement with the experimental values. Therefore, by looking at the HFS results, we can say that both E-eff and W-s values are also very accurate. Further, We have derived the relationship between these quantities and the ratio which will help to get model independent value of eEDM and S-PS interaction constant. (C) 2016 AIP Publishing LLC.

Shape resonance of sulphur dioxide anion excited states using the CAP-CIP-FSMRCCSD method - Basumallick, Suhita; Bhattacharya, Sumantra; Jana, Irina; Vaval, Nayana; Pal, Sourav (Molecular Physics, 2020)
We have studied the shape resonance of excited states of sulphur dioxide (SO2) anion by using the correlated independent particle Fock space multi-reference coupled cluster (CAP-CIP-FSMRCCSD) method augmented by complex absorption potential. These resonant states have been trapped experimentally in recent years by electron collision. In particular, we have investigated e(-)-SO2 scattering and computed the negative-ion resonance states of the anion responsible for the two resonances around 4.45 and 6.56 eV and compared the results with the existing experimental observations. From the computational results using the CAP-CIP-FSMRCCSD method, it has been observed that both the resonances near 4.45 and 6.56 eV result from A(1) symmetries. [GRAPHICS] .
Keywords: CAP augmented correlated independent particle (CAP-CIP-FSMRCCSD); complex absorption potential (CAP); coupled cluster; Fock space multireference coupled cluster (FSMRCCSD); shape resonance

Synthesized novel chromogenic reagent and sensor: detection and identification of dichlorvos - Gedam, Ashwin D.; Katiya, Manish M.; Dhonde, Madhukar G.; Ganorkar, Kapil S.; Thakare, Vijay J.; Mandlik, Prashant R.; Jadhao, Nitin L.; Gajbhiye, Jayant M.; Kumar, Ravi; Vaval, Nayana (Heliyon, 2024)
We developed a novel chromogenic reagent and sensor by selective approach, for the detection and identification of dichlorvos, which we tested with the thin layer chromatography method. For the first time, we reported in situ-generated glyoxal as a hydrolysis product, which then interacts with isoniazid to produce a yellow-colored cyclic compound. We used well-known spectroscopic techniques to confirm the chemical identity of the final product. We initially investigated the reaction using a variety of approaches, followed by attempts to establish the reaction mechanism using Density Functional Theory by Gaussian software.
Keywords: DFT analysis; Dichlorvos; Gloyxal; Hydrazone; Isoniazid